Application of Artificial Intelligence in Radiological Image Analysis for Pulmonary Disease Diagnosis: A Review of Current Methods and Challenges - Karolina Zalewa; Joanna Olszak; Wojciech Kapłan; Dominika Orłowska; Lidia Bartoszek; Marta Kaus; Natalia Klepacz (Journal of Education, Health and Sport)
Introduction and purpose Artificial intelligence (AI), particularly machine learning (ML) and deep learning (DL), is revolutionizing radiology by improving diagnostic accuracy and efficiency. This paper examines AI applications, especially convolutional neural networks (CNNs), in diagnosing pulmonary diseases, such as pneumonia, tuberculosis, and lung cancer. The goal is to explore the impact of these technologies and assess challenges in their integration into clinical practice.